Tariq Ramadan's Concept of Tolerance and the Muslim Identity Crisis: An Islamic Psychological Perspective - Henri Shalahuddin; Ihsan Abdul Aziz (Jurnal Theologia, 2025)
This article examines the concept of tolerance in Tariq Ramadan's thought as a solution to the identity crisis faced by contemporary Muslims, making Ramadan's tolerance the primary unit of analysis. This research aims to examine how the construction of tolerance offered by Ramadan—which is rooted in Islamic spirituality, dialogue ethics, and psychological awareness—can serve as a framework for restoring the Muslim identity amidst the dynamics of globalization, plurality, and modern cultural pressures. Utilizing library research methods with a qualitative, descriptive, and analytical approach, as well as content analysis, this study examines primary works by Ramadan, along with relevant secondary literature on tolerance, Muslim identity, and Islamic psychology. The study's findings reveal that Ramadan rejects the model of passive tolerance based on power relations and proposes an alternative model of active tolerance, grounded in tawhid, the recognition of God's will in diversity, and the integration of qalb, reason, and social ethics. An analysis of Islamic psychology reveals that tolerance within the framework of Ramadan has a spiritual dimension that can help overcome the crises of meaning, alienation, and identity polarization. The contribution of this research lies in presenting a conceptual model of tolerance with Islamic psychological nuances that can serve as the basis for strengthening Muslim identity, as well as the development of educational, counseling, and intergroup dialogue practices in multicultural societies.